ANALYSIS OF VISUAL ELEMENTS AND RESPONSES OF GENERATIONS Z ON LAMBORGHINI COMMERCIAL VIDEO - Daniel Haingu; I Gede Tangkas Yoganandita; Putu Chrisma Dewi; Putu Chris Susanto (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2021)
ABSTRACTVideo advertising is a form of advertisement for a product or service that uses videoto expand the product. Video advertising is general because it is interesting andmemorable for the public. This study aims to analyze one particular advertisingmedia in the form of video used by Lamborghini brand of automobile manufacturerdepicting everyday life using visual grammar analysis, and to examine theresponses of Indonesian Generation Z on that video using a descriptivequalitative approach. In addition to analysis of visual grammar using the analysis toolsby Kress and van Leeuwen, video elicitation interviews were conducted with fiveparticipants to further explore the effectiveness of the visual elements from theperspective of Generation Z using the Hierarchy of Effects model of determiningadvertising effectiveness, paying close attention to the response on the meaningfulnessof the visual advertising campaign.Keywords: video advertising, visual elements, generation z, visual grammar, photoelicitation